Partitioning of Water Between Differently Sized Shrubs and Potential Groundwater Recharge in a Semiarid Savanna in Namibia - Geißler, Katja; Heblack, Jessica; Uugulu, Shoopala; Wanke, Heike; Blaum, Niels (Frontiers in Plant Science, 2019)
Introduction: Many semiarid regions around the world are presently experiencing significant changes in both climatic conditions and vegetation. This includes a disturbed coexistence between grasses and bushes also known as bush encroachment, and altered precipitation patterns with larger rain events. Fewer, more intense precipitation events might promote groundwater recharge, but depending on the structure of the vegetation also encourage further woody encroachment. Materials and Methods: In this study, we investigated how patterns and sources of water uptake of Acacia mellifera (blackthorn), an important encroaching woody plant in southern African savannas, are associated with the intensity of rain events and the size of individual shrubs. The study was conducted at a commercial cattle farm in the semiarid Kalahari in Namibia (MAP 250 mm/a). We used soil moisture dynamics in different depths and natural stable isotopes as markers of water sources. Xylem water of fifteen differently sized individuals during eight rain events was extracted using a Scholander pressure bomb. Results and Discussion: Results suggest the main rooting activity zone of A. mellifera in 50 and 75 cm soil depth but a reasonable water uptake from 10 and 25 cm. Any apparent uptake pattern seems to be driven by water availability, not time in the season. Bushes prefer the deeper soil layers after heavier rain events, indicating some evidence for the classical Walter’s two-layer hypothesis. However, rain events up to a threshold of 6 mm/day cause shallower depths of use and suggest several phases of intense competition with perennial grasses. The temporal uptake pattern does not depend on shrub size, suggesting a fast upwards water flow inside. δ2H and δ18O values in xylem water indicate that larger shrubs rely less on upper and very deep soil water than smaller shrubs. It supports the hypothesis that in environments where soil moisture is highly variable in the upper soil layers, the early investment in a deep tap-root to exploit deeper, more reliable water sources could reduce the probability of mortality during the establishment phase. Nevertheless, independent of size and time in the season, bushes do not compete with potential groundwater recharge. In a savanna encroached by A. mellifera, groundwater will most likely be affected indirectly.